2012
DOI: 10.12693/aphyspola.122.732
|View full text |Cite
|
Sign up to set email alerts
|

Planar Photonic Crystals Biosensor Applications of TiO2

Abstract: We examine quality factor and sensitivity change depending on the resonant wavelength changing refractive index of surrounding liquid for TiO2 photonic crystal slab structure. Photonic crystal slab structure is used widely for biological materials such as proteins, antigens, DNA, cells, virus particles and bacteria. Mentioned photonic crystal slabs are usable with large-area biosensor designs. They permit direct access to externally incident optical beams in a microuidic device. Model calculations are based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The W1 waveguide is formed by removing a row of holes in the Γ K direction. Recently, it has been shown that air-suspended membrane-type PCs have a greater sensitivity than PC slabs on a substrate due to the higher refractive index contrast [21]. Therefore, the Si PC slab (n = 3.47) in our study is suspended in air.…”
Section: Design and Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…The W1 waveguide is formed by removing a row of holes in the Γ K direction. Recently, it has been shown that air-suspended membrane-type PCs have a greater sensitivity than PC slabs on a substrate due to the higher refractive index contrast [21]. Therefore, the Si PC slab (n = 3.47) in our study is suspended in air.…”
Section: Design and Modelingmentioning
confidence: 99%
“…By performing 2D FDTD calculations with an e ective index method for a PCW slab, it was found that substitution of all the PC air holes with water signi cantly enhances the sensing performance in comparison to substitution of the cladding layer [21]. Later, it was reported that in ltration of only the rst rows of holes adjacent to the line-defect with water enhances the sensitivity greater than the in ltration of all lattice holes [18].…”
Section: Design and Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…In the few last decades, the raised of utilized from the photocatalysts and nanocatalysts was regarded as versatile materials such as produced of solar cells [1][2], decolorized and degradation of organic compounds [3][4][5][6][7][8] used as biosensor [9][10], synthesis some organic compounds in certain reactions [11], using as anticancer and antitumor [12][13], and using in SPF solar emulsions as sunscreen [14][15].…”
Section: ■ Introductionmentioning
confidence: 99%
“…As a kind of artificial smart material, responsive photonic crystals (PCs), whose optical properties can be tuned in response to external stimuli, have recently evoked a lot of interest due to their applications in stimuli-responsive sensing devices, color-changing paints and inks, and photonic active elements. It is well-known that applying the external stimuli could lead to changes in the effective refractive index, ,, the lattice parameter, , and/or the order degree of the PC structures, allowing for the reversible switching of the photonic band gap (PBG) of responsive PCs.…”
Section: Introductionmentioning
confidence: 99%